Why do the urgency of stakeholders matter more in the firm performance? - Maqsood Hayat; Dr. Shehzad Khan; Kiran Alim (Journal of Business & Tourism, 2021)
This study is an attempt to scrutinize the importance of different stakeholders with respect to financial performance (FP hereafter) in emerging countries context. Unlike developed countries, every element of the corporate social responsibility (CSR hereafter) is not supposed to generate similar corporate payback in the context of developing countries. Enterprises take considerable care to categorize these stakeholders in proper sequence for better corporate results. It was found empirically that CSR disclosure (CSRD hereafter) relevant to employees and communities have direct relationship with the firm‟s performance in term of earning per share (EPS).The results of this study will portray a comprehensive picture for corporate decision makers to realize the priorities and urgency of different beneficiaries for corporate benefits, existence and prosperity in the context of developing countries like Pakistan.